Soggetto in Ombra (Milano : Casa degli Artisti, 1998)
Aicardi, Caterina ; Bellicini, Francesca ; Cantoni, Silvia ; Cella, Stefania ; Citterio, Claudio ; Francesconi, David ; Juhas, Daniel ; Orlandi, Michele ; Palumbo, Nicola ; Reitano, Paolo ; Schwaighofer, Pascal ; Tavola, Alessandra ; Trombetta, Luciana ; Kun, Wilma
Soggetto in Ombra, Casa degli Artisti, Milano, 9, 15 Luglio 1998
kunstcatalogus